Common or divided security? : German and Norwegian perspectives on Euro-Atlantic security - Allers, Robin M., 1970-; Masala, Carlo; Tamnes, Rolf (Peter Lang, 2014)
"Twenty-five years after the end of the Cold War, Euro-Atlantic security is under pressure. Faced with major geopolitical shifts, instability at its frontiers and financial crisis at home, the European nations and their American Allies will have to rethink how to design common security. Failure to animate the European Union (EU) and to reinvigorate the North Atlantic Treaty Organisation (NATO) as efficient tools for peace and security might lead the West back to the spectre of divided security, to fragmentation and renationalisation. This book addresses the main challenges to Western security from the perspective of two European Allies: Germany and Norway"--Provided by publisher.